1985
DOI: 10.1111/j.1365-2265.1985.tb01083.x
|View full text |Cite
|
Sign up to set email alerts
|

Endocrine Effects of Low Dose Aminoglutethimide as an Aromatase Inhibitor in the Treatment of Breast Cancer

Abstract: The endocrine effects of low dose (62.5 mg, twice a day) aminoglutethimide (AG), without hydrocortisone (HC), escalating at monthly intervals to a conventional dose of AG (500 mg twice a day) combined with HC, were studied in 33 postmenopausal breast cancer patients. Pretreatment serum concentrations of oestrone (E1) and oestradiol (E2) were significantly suppressed by 62.5 mg of AG twice a day. Although further suppression of E1 appeared to occur with 125 mg of AG twice a day, this was not statistically signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

1988
1988
1999
1999

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 31 publications
0
11
1
Order By: Relevance
“…This is in contrast to the data on aminoglutethimide which, when used without glucocorticoids, significantly inhibits 1lp-hydroxylase and 18-hydroxylase at therapeutic doses (Santen et al, 1981) and causes increases in the levels of the androgenic precursors of aromatase (Harris et al, 1983a;Stuart-Harris et al, 1985). We have also found that CGS 16949A causes a significant suppression of aldosterone levels at therapeutic doses (1 mg and 2 mg b.d.)…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This is in contrast to the data on aminoglutethimide which, when used without glucocorticoids, significantly inhibits 1lp-hydroxylase and 18-hydroxylase at therapeutic doses (Santen et al, 1981) and causes increases in the levels of the androgenic precursors of aromatase (Harris et al, 1983a;Stuart-Harris et al, 1985). We have also found that CGS 16949A causes a significant suppression of aldosterone levels at therapeutic doses (1 mg and 2 mg b.d.)…”
Section: Discussioncontrasting
confidence: 55%
“…The related drug aminoglutethimide has been noted to enhance the clearance of oestrone sulphate (Lonning et al, 1989). There is also an unexplained minor fall in DHAS levels in patients on aminoglutethimide without replacement glucocorticoid which is coincident with increases in unconjugated androgens (due to the inhibition of 11p-hydroxylase) (Stuart Harris et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…In both of these patient groups the adrenal glands are the major source of circulating androgens. However, it has previously been demonstrated that in postmenopausal patients AG given alone results in increased plasma levels of androstenedione and testosterone (Harris et al, 1983a;Vermeulen et al, 1983;Stuart-Harris et al, 1985) and when given in combination with HC results in a less extensive suppression of the androgens than HC given alone . The results in this study indicate that the effects of AG and HC when given alone or in combination to previously orchiectomized prostatic cancer patients are similar to those observed in the studies of postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…The demonstration that aminoglutethimide (AG) inhibited the conversion of cholesterol to pregnenolone (Dexter et al, 1967) led to the use of the drug in combination with hydrocortisone (HC) as a so-called 'medical adrenalectomy' in postmenopausal breast cancer patients (Santen et al, 1974) and also with some apparent benefit in prostate cancer patients (Robinson et al, 1974). The mechanism of action of this combination in prostatic cancer has been questioned, since HC is itself an adrenal suppressant and AG is now accepted as acting by aromatase inhibition in breast cancer patients (Santen et al, 1978;Stuart-Harris et al, 1984). When used alone in postmenopausal patients AG causes an increase in androgen levels (Harris et al, 1983a;Vermeulen et al, 1983;StuartHarris et al, 1985).…”
mentioning
confidence: 99%
“…Side effects, including skin rash, drowsiness and the inhibition of cortisol synthesis, necessitated the use of corticosteroids with their concomitant side effects. This led to various studies in which lower doses of aminoglutethimide were used in the treatment of patients with breast cancer (Harris et al 1983, Stuart-Harris et al 1985. However, the responses seen were generally lower and the duration of response was reduced, although formal trials comparing different dose regimens and using sufficient numbers of patients to provide the necessary statistical power have not been adequately carried out.…”
Section: Introductionmentioning
confidence: 99%